The Challenges of Implementing the Independent Curriculum in Facing Technological Developments in the Era of the Industrial Revolution 4.0 - Sinulingga, Sehat (PPSDP International Journal of Education, 2023)
The goal of this study was to evaluate how well the autonomous curriculum was being used to address technical advancements in the era of the fourth industrial revolution. The descriptive qualitative methodology is used in this study. Utilizing interviews, documentation, and literature reviews as a data collection method. The study’s findings revealed that: 1) school assessments, character assessments, an effective zoning system called RPP, and the implementation of report cards made up the independent learning curriculum; and 2) the difficulties of implementing an independent curriculum in the face of technological advancements in the industrial era 4.0 are more closely related to the implementation of learning, including the demands for the availability of adequate infrastructure, the competence of teachers, and the independence of educational institutions.